CORNEAL ENDOTHELIAL CELL CHANGES AFTER PARS PLANA VITRECTOMY; SILICONE VERSUS NON-SILICONE FILLED EYES AND THE EFFECT OF LENS STATUS - Sohaib Abbas; Muhammad Awais Asghar; Naseer Ahmad; Abdul Munim; Arslan Ahmed; Faisal Nawaz (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The aim of the study was to determine Corneal Endothelial Cell Changes after Pars Plana Vitrectomy; Silicone oil versus non-silicone oil oil-filled eyes and the effect of Lens status. Materials and Method; 60 eyes are included in this prospective observational study and are split into two equal groups: group A, silicone oil-filled, and group B, saline-filled.  Preoperatively, as well as the first week, first month, and third month postoperatively, endothelial cell densities (ECD), central corneal thickness (CCT), coefficient of variation (CV), and proportion of hexagonal-shaped cells at the eyelid center were measured and compared between the two groups. The SPSS software was used to gather and statistically analyze all of the data. Results; Three months following PPV, both group A and group B mean ECDs were extremely significant, with the first week following surgery seeing the largest drop in cell count. Though more impacted in group A, the difference in endothelial cell loss between each of the groups was clinically negligible. Conclusions; Pars plana vitrectomy (PPV) was linked to alterations in corneal endothelial cells, although these differences were not statistically significant. Patients with Silicone oil-filled eyes had higher levels of these changes than those who were left with saline. After PPV, silicone oil may increase the risk of endothelial cell loss.